Digital identity management - Laurent, Maryline; Bouzefrane, Samia (London : ISTE Press Ltd ; Oxford : Elsevier Ltd, 2015)
In the past four decades, information technology has altered chains of value production, distribution, and information access at a significant rate. These changes, although they have shaken up numerous economic models, have so far not radically challenged the bases of our society.
4.5. Research Themes 4.6. Conclusions ; 4.7. Bibliography ; Chapter 5: Digital Identity in Cloud Computing ; 5.1. Introduction ; 5.2. Concepts of Cloud Computing ; 5.3. Other Key Characteristics of Cloud Computing ; 5.4. Classic Solutions for Digital Identity Management in the Cloud ; 5.5. Alternative Solutions for Digital Identity Management in the Cloud ; 5.6. Management of Privacy and Personal Data in Cloud Computing ; 5.7. Conclusion ; 5.8. Bibliography ; List of Authors ; Index.
Includes bibliographical references and index.
Vendor-supplied metadata.
Keywords: Data protection; Computer networks -- Security measures; Computer networks -- Access control; COMPUTERS -- Security -- General; TECHNOLOGY & ENGINEERING -- Electronics -- Digital; Computer networks -- Access control; Computer networks -- Security measures; Data protection; Electronic books; Electronic books